2020
DOI: 10.1080/26415275.2020.1711760
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of resin- and varnish-based surface protective agents on glass ionomer cement – a spectrophotometric analysis

Abstract: Objectives: To evaluate and compare the effectiveness of resin-and varnish-based surface protective agents on Glass Ionomer Cement (GIC). The different surface protective agents used were: Vaseline V R , GC Fuji VARNISH TM (varnish), G-Coat Plus TM (resin) and EQUIA V R Coat (resin). Method: Thirty-six identical specimens of GIC were made. Six specimens were used in preparation of standard solution and remaining thirty were divided into five groups with six specimens in each group. Each test specimen was coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The NHC material includes, cross-linked inorganic macro fillers, micro fillers, and silicon dioxide in nanoscale size (28,29) . The development of micro filler-containing composites eliminated the problems related to the rough surface consistency also, highly discrete silicon dioxide with mean particle size of 40 nm, considered as suitable material for removing rough surfaces (30) . It can be observed that surface roughness showed a significant decrease for all tested samples among different solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The NHC material includes, cross-linked inorganic macro fillers, micro fillers, and silicon dioxide in nanoscale size (28,29) . The development of micro filler-containing composites eliminated the problems related to the rough surface consistency also, highly discrete silicon dioxide with mean particle size of 40 nm, considered as suitable material for removing rough surfaces (30) . It can be observed that surface roughness showed a significant decrease for all tested samples among different solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies founds Fuji II LC (resin modified glass ionomer) without coating less microleakage than Fuji IX (conventional glass ionomer) without coating because resin-modified GIC (RMGIC) has resin monomers, like HEMA or Bis-GMA incorporated in its composition, making it higher flexural, compressive, and tensile strengths than conventional GICs (27,28,29) thus in this study the coating give improve to the Fuji IX become the same degree of microleakage to the Fuji II LC without coating.…”
Section: Discussionmentioning
confidence: 99%
“…19 Glass ionomer cement was manipulated according to the manufacturer's instructions using High Speed Mixer HSM3 for 10 seconds, then placed into the mold with capsule applier. 17,18,20 The restoration was covered with a mylar strip, a glass preparation, and a 200 g load for 7 minutes to ensure the initial hardening. 17,20,21 Excess material was removed using scalpel and blade.…”
Section: Methodsmentioning
confidence: 99%
“…15 Therefore, the use of coating agents, like varnishes, emollients, or resins is important to protect glass ionomer cement from acids. 4,16 Tyagi et al 17 , states that varnish is the most superior coating agent material in terms of cost with better protection capabilities than emollients and and has the same protection capability as resin at a higher price. Unfortunately many dentists neglected this procedure.…”
Section: Introductionmentioning
confidence: 99%